Cost-effectiveness of the endovascular repair: of Abdominal Aortic Aneurysm in Portugal - Sousa,Paulo (2014)
Endovascular Aneurysm Repair (EVAR) for the treatment of aortic abdominal aneurism has been shown to improve short-term survival and quality of life as compared to Open Repair (OR), while reducing the rate of serious complications and allowing for the treatment of more patients. Objectives: To examine the cost-effectiveness of EVAR compared to OR in the treatment of aortic abdominal aneurism in the Portuguese context using a model previously developed in the UK. Methodology: We adapted an international economic evaluation model to the Portuguese situation, assuming that the health benefits of EVAR observed in clinical trials would also apply to Portuguese patients. We carried out an expert panel survey to calculate the resource use associated with the intervention and its short and long-term consequences, valued with Portuguese prices. Results: The major cost difference in the primary intervention (difference of 3,064 in favor of OR) is related to the cost of the endograft/graft. No major differences are observed in the total cost of complications and re-interventions between the two procedures. EVAR represents a cost of 16,709 over lifetime compared to 12,130 for OR. Using data from the literature we show that EVAR allows for 0.17 additional undiscounted years of life and 0.091 additional undiscounted quality-adjusted life years. The incremental cost-effectiveness ratio (ICER) of EVAR is of 65,605 /QALY. Conclusion: Endovascular repair of aortic abdominal aneurysm represents an effective alternative and has been used increasingly in Portugal and elsewhere. Our study shows that its cost-effectiveness is currently above the commonly accepted threshold in Portugal, but that the economic value of EVAR would greatly improve if benefits were confirmed in the long run after the intervention. Under these circumstances, EVAR would become an economically valuable intervention that could be adopted on a large scale in Portugal.